How do you take the derivative of y=tan^2(x^3)y=tan2(x3)?

1 Answer
Aug 21, 2015

y^' = 6x^2 * tan(x^3) * sec^2(x^3)

Explanation:

You can differentiate this function by using the chain rule twice, once for u^2, with u = tan(x^3), and once more for tan(t), with t = x^3.

This will get you

d/dx(y) = d/(du)u^2 * d/dx(u)

y^' = 2u * d/dxtan(x^3)

The derivative of tanx^3 will be equal to

d/dx(tant) = d/(dt)tan(t) * d/(dx)(t)

d/dx(tant) = sec^2t * d/dx(x^3)

d/dx(tan(x^3)) = sec^2(x^3) * 3x^2

Your target derivative will thus be equal to

y^' = 2 * tan(x^3) * 3x^2 * sec^2(x^3)

y^' = color(green)(6x^2 * tan(x^3) * sec^2(x^3))